Humanoid Gait Optimization Resorting to an Improved Simulation Model. (25th January 2013) - Lima, José L.; Gonçalves, José A.; Costa, Paulo G.; Moreira, A. Paulo
The simulation of a robot with a high number of joints can easily become unstable. Numerical errors on the first joint of the chain are propagated to the other joints. This is a very common problem in humanoid robots. A way to plan the gait for these robots is using simulation and optimization techniques. This paper addresses a new approach to optimizing gait parameter sets using an adaptive simulated annealing optimization algorithm, combined with a new joint model that reduces its instability. The new model and the optimization are implemented in SimTwo (a developed physical robot simulator that is capable of simulating user defined robots in a three-dimensional space, since it includes a physical model based on rigid body dynamics) and results are shown that validate the approach.